Incremental validity of Useful Field of View subtests for the prediction of instrumental activities of daily living. Issue 5 (27th May 2016) - Aust, Frederik; Edwards, Jerri D.
ABSTRACT: Introduction : The Useful Field of View Test (UFOV®) is a cognitive measure that predicts older adults' ability to perform a range of everyday activities. However, little is known about the individual contribution of each subtest to these predictions, and the underlying constructs of UFOV performance remain a topic of debate. Method : We investigated the incremental validity of UFOV subtests for the prediction of Instrumental Activities of Daily Living (IADL) performance in two independent datasets, the SKILL ( n = 828) and ACTIVE ( n = 2426) studies. We then explored the cognitive and visual abilities assessed by UFOV using a range of neuropsychological and vision tests administered in the SKILL study. Results : In the four subtest variant of UFOV, only Subtests 2 and 3 consistently made independent contributions to the prediction of IADL performance across three different behavioral measures. In all cases, the incremental validity of UFOV Subtests 1 and 4 was negligible. Furthermore, we found that UFOV was related to processing speed, general nonspeeded cognition, and visual function; the omission of Subtests 1 and 4 from the test score did not affect these associations. Conclusions : UFOV Subtests 1 and 4 appear to be of limited use to predict IADL and possibly other everyday activities. Future research should investigate whether shortening UFOV by omitting these subtests is a reliable and valid assessment approach.